2006
DOI: 10.3748/wjg.v12.i38.6219
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer to the gastrointestinal tract: A case series and review of the literature

Abstract: Metastatic breast cancer involving the hepatobiliary tract or ascites secondary to peritoneal carcinomatosis has been well described. Luminal gastrointestinal tract involvement is less common and recognition of the range of possible presentations is important for early and accurate diagnosis and treatment. We report 6 patients with a variety of presentations of metastatic breast cancer of the luminal gastrointestinal tract. These include oropharyngeal and esophageal involvement presenting as dysphagia with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
115
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 59 publications
4
115
0
3
Order By: Relevance
“…Despite breast cancer metastases to the gastrointestinal tract being less common than to other sites, because breast cancer is extremely common, it may be responsible for a high proportion of metastatic gastric tumors. In the present study, the pathological results for both breast cancer patients showed invasive lobular carcinoma, which agrees with findings reported previously (4,8). As tumor histology is one of the predictors of metastatic spread, lobular carcinoma is more likely to metastasize to the gastrointestinal tract, although metastatic gastric tumors are less common than ductal carcinoma and the mechanisms involved are not clear (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite breast cancer metastases to the gastrointestinal tract being less common than to other sites, because breast cancer is extremely common, it may be responsible for a high proportion of metastatic gastric tumors. In the present study, the pathological results for both breast cancer patients showed invasive lobular carcinoma, which agrees with findings reported previously (4,8). As tumor histology is one of the predictors of metastatic spread, lobular carcinoma is more likely to metastasize to the gastrointestinal tract, although metastatic gastric tumors are less common than ductal carcinoma and the mechanisms involved are not clear (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the pathological results for both breast cancer patients showed invasive lobular carcinoma, which agrees with findings reported previously (4,8). As tumor histology is one of the predictors of metastatic spread, lobular carcinoma is more likely to metastasize to the gastrointestinal tract, although metastatic gastric tumors are less common than ductal carcinoma and the mechanisms involved are not clear (8)(9)(10). These results emphasize the importance of considering metastatic gastric cancer, especially in patients with a previous history of breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…This study reaffirms the fact that despite lobular carcinoma being less common than ductal; it more frequently metastasizes to the GI tract [11,12,20,24]. Interestingly, 5-15% of patients have metastases when they are diagnosed with breast cancer [25].…”
Section: Discussionsupporting
confidence: 78%
“…Other studies ranged from 4.4 to 9.5 years [11,20,24,26]. Because breast cancer patients follow with an oncologist only sporadically after diagnosis and first treatment, it is important for these patients to follow with a general practitioner, such as an Internist or Family Physician.…”
Section: Discussionmentioning
confidence: 99%
“…There is diffuse intramural infiltration of the gastric wall by the tumor; this results in narrowing of the stomach lumen, rigidity, and diminished peristalsis [14] . The average presentation timebetween the initial breast cancer diagnosis and the gastrointestinal metastatic disease presentation is 6-9 years [15,16] .…”
Section: Discussionmentioning
confidence: 99%